2001
DOI: 10.1063/1.1410981
|View full text |Cite
|
Sign up to set email alerts
|

A classification method for vortex sheet and tube structures in turbulent flows

Abstract: A new classification method for structures in turbulent flow is proposed and applied to the analysis of homogeneous isotropic turbulence. The criteria for the classification of the structures into three groups, namely, the group of structures similar to the core region of the Burgers’ vortex tube in which vorticity is predominant, that of the structures similar to the curved sheet in the circumference of the tube core in which strain is predominant, and that of the flat sheets similar to the Burgers’ vortex la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
1
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 27 publications
1
42
1
1
Order By: Relevance
“…In turbulent flows, the regions of concentrated vorticity consist of either (i) vortical tube-like structures (vortex tubes) or in (ii) structures exhibiting a sheetlike shape (vortex sheets) [20]. Whereas in the tube-like structures, vorticity and strain are comparable, the sheet-like structures are dominated by vorticity with relatively low levels of strain.…”
Section: (B) the Coherent Vortices Near The Turbulent/non-turbulent Imentioning
confidence: 99%
“…In turbulent flows, the regions of concentrated vorticity consist of either (i) vortical tube-like structures (vortex tubes) or in (ii) structures exhibiting a sheetlike shape (vortex sheets) [20]. Whereas in the tube-like structures, vorticity and strain are comparable, the sheet-like structures are dominated by vorticity with relatively low levels of strain.…”
Section: (B) the Coherent Vortices Near The Turbulent/non-turbulent Imentioning
confidence: 99%
“…Andreotti (1997) showed that the tendency for the vorticity vector to align with the intermediate strain-rate eigenvector is a result of the crossover of the eigenvalues. This led to the development of an alternative reordering of the eigenvalues in which the eigenvalue with the corresponding eigenvector that is most closely aligned with the vorticity vector is denoted σ z , with the largest of the two remaining eigenvalues denoted σ + and the smallest one denoted as σ − (Andreotti 1997;Nomura & Post 1998;Horiuti 2001). However, in the current study, the eigenvalues would have more physical meaning when arranged by magnitude as it would be clear that the corresponding eigenvector would be compressive, extensive or alternate.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of identification methods (local and non-local) are devoted to educing those types of structures. Traditionally, more attention has been paid to tube-like structures, but recently considerable interest has put forward the eduction of sheet-like structures (see, for example, Tanaka & Kida 1993;Horiuti 2001). Local methods targeted at educing tubes and sheets, based on physical principles, resort often to visualization of the regions of joined classified points to assess the geometrical character of those regions.…”
Section: Introductionmentioning
confidence: 99%